\(3-\dfrac{1}{4}+3\dfrac{2}{3}=3-\dfrac{1}{4}+\dfrac{11}{3}=\dfrac{36}{12}-\dfrac{3}{12}+\dfrac{44}{12}=\dfrac{36-3+44}{12}=\dfrac{77}{12}\)
` 3- 1/4 + 3 2/3= 3 - 1/4 + 11/3= 12/4 -1/4 + 11/3=11/4 +11/3= 33/12 + 44/12=77/12`
\(3-\dfrac{1}{4}+3\dfrac{2}{3}=\dfrac{11}{4}+\dfrac{11}{3}=\dfrac{77}{12}\)
\(3-\dfrac{1}{4}+3\dfrac{2}{3}=3-\dfrac{1}{4}+\dfrac{11}{3}=\dfrac{3}{1}-\dfrac{1}{4}+\dfrac{11}{3}=\dfrac{36}{12}-\dfrac{3}{12}+\dfrac{44}{12}=\dfrac{77}{12}\)
`3 - 1/4 + 3 2/3 = 3 - 1/4 + 11/3 =36/12-3/12+44/12=(36-3+44)/12=77/12`